Partisipasi Masyarakat Dalam Pelestarian Hutan Lindung Bontang: Upaya Pencegahan Kebakaran Hutan dan Lahan - Muhammad Nasir (Jurnal Loupe, 2017)
Forest fires in East Kalimantan almost always occur in very dry season. Therefore, forests and land, especially protected areas such as Bontang Protected Forest require the attention and participation of surrounding communities. The objectives of this study were: to analyze community perception of Bontang Protected Forest area, analyze community participation in conservation efforts, and forest fire prevention efforts in Bontang Protected Forest. The results indicated that perception of community about Bontang Protected Forest area is very good. The community has understood the benefits of protected forest, as well as on the community’s dependence on forests and land. Similarly, community participation in forest fire prevention, they have been proven to participate actively.